2021
DOI: 10.1155/2021/2724743
|View full text |Cite
|
Sign up to set email alerts
|

Study on Dispersion Stability and Friction Characteristics of C60 Nanomicrosphere Lubricating Additives for Improving Cutting Conditions in Manufacturing Process

Abstract: Antifriction lubrication is an important research hotspot in the manufacturing field. A high-performance lubricating additive is of great significance for condition monitoring in the metal cutting process system. To improve cutting conditions in manufacturing process, we study the dispersion stability and tribological properties of fullerene nanoparticles in HM32 antiwear lubricating fluid. Fullerene nanoparticles are fully integrated into HM32 antiwear lubricating fluid by electromagnetic stirring and ultraso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…This result confirms that MoS 2 /C 60 has the best wear resistance among the three additives. From Figure 8(c), it can be seen that the friction surface after DOS lubrication containing C 60 is flatter relative to that after pure DOS lubrication, and there are almost no pits and grooves appearing on the wear surface, which is related to the fact that C 60 enters into the friction interface and improves the interfacial load-bearing capacity (Huang et al , 2021).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…This result confirms that MoS 2 /C 60 has the best wear resistance among the three additives. From Figure 8(c), it can be seen that the friction surface after DOS lubrication containing C 60 is flatter relative to that after pure DOS lubrication, and there are almost no pits and grooves appearing on the wear surface, which is related to the fact that C 60 enters into the friction interface and improves the interfacial load-bearing capacity (Huang et al , 2021).…”
Section: Resultsmentioning
confidence: 99%
“…From Figure 5(e)–5(f), it can be clearly seen that the absorbance values of the C 60 and MoS 2 /C 60 suspensions slightly decreased with the increase of the standing time, but the change was not significant, which indicated that the concentration of C 60 and MoS 2 /C 60 nanoparticles did not change significantly and the dispersion stability was good. This may be since fullerene C 60 has a certain aromaticity and can be well dissolved in organic solvents (Huang et al , 2021). The absorbance of the MoS 2 suspensions varied greatly, with 60% of the absorbance of the suspensions left for 20 days compared with the newly configured suspensions, which is consistent with the results of the conventional sedimentation experiments.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…At present, the research on cutting friction and tool wear focuses on improving lubrication and cooling conditions [6][7][8], tool wear mechanisms [9][10][11], and tool wear monitoring [12][13][14]. The contact friction system between the tool and the workpiece in the cutting process is a nonlinear chaotic dynamic system.…”
Section: Introductionmentioning
confidence: 99%